Przymusowa kartelizacja przemysłu II Rzeczypospolitej w latach 1925-1933 - Łapa, Małgorzata (Acta Universitatis Lodziensis. Folia Historica, 1997)
One of more important issues, concerning industry of the Polish Republic II, was state policy towards obligatory cartels. After J. Pilsudski's coup d’etat sanacja authorities, having an interest to win business spheres’ support, exposed its positive attitude towards cartels. Number of cartels grew rapidly since 1925. An economic importance of cartels increased and the main branches of economy were comprised by the cartelization. The Government had an influence on cartels agreements. The state interventionism in economy, tending to the obligatory cartelization, appeard in using proper policy of customs, credits and tarrifs towards some branches of industry. The Government had also a direct influence on organizational matters of some cartels. This interference appeared in special legal acts for exemple, which changed organizational structures of cartels or created new ones. Between 1925 and 1933 the coal, sugar, textile and alcohol industries were obligatory cartelized among others. The Government tended to subordinate main branches of industry in result of a conviction that cartels should prevent a disorder of domestic market and should be an effective instrument of economic policy, creating an economic balance and a rapid industralization of Poland.